Enhancing the productivity of sales visit in b2b context and the company business process: a study at pt ala, distributor of fmcg product - Adli Putra, Muhammad; Furinto, Asnan (The Indonesian Journal of Business Administration, 2019)
Abstract - Product distribution is an essential part for any FMCG products as it’s a doorway that connect the products with their consumer. The problems arise during the research is that the sales productivity aren’t maximize and the business process is not efficient, resulting in lower number of effective call (EC) for wholesale compare to retail. The wider the distribution of a certain product, the easier it is for the consumer to access that said product. Nowadays, products are distributed into two markets; modern and traditional. The modern market consisted of hypermarket, supermarket and minimarket while the traditional market consist of retail and wholesale. This research used both quantitative and qualitative method. The quantitative method is through the analysis of salesman visit data during the month of August 2018 at the Leteng Agung Depot. While the qualitative is obtained through observation during the process of joint call and in the form of questionnaires and interview about their satisfaction towards the services provided by PT ALA. The macro-environment analysis is done by using PESTLE analysis, where the Politic, Economic, Social, Technological, Law and Environment factors were analyzed. Afterwards, the attractiveness of the industry is identified through Porter’s Five Forces where it looks how powerful are the customer and supplier bargaining power, the threat of substitute and new entrants into the industry and lastly the existing competitor. The proposed solution to the problem is to implement an application based system for the customer that have the functions of online order, delivery tracking, invoice, product return request and chat with salesman. The system will improve salesman productivity and improve business process efficiency. Keywords: B2B, distribution, development strategy, Online order, Porter’s Five Forces